La letteratura in laboratorio Literature in the Laboratory - Franco Moretti (digitalis purpurea: Saggi di Digital Humanities in Letteratura, Linguistica, Filologia, 2019)
Literature in Laboratory is a collection of 12 Pamphlets published by the Stanford Literary Lab under the direction of its founder, Franco Moretti, from 2011 to 2017. Already translated into several languages, Moretti's Literary Lab Pamphlets have opened up a new chapter in the fields of literary and digital studies by creating a new way of critically approaching texts. Moretti and his group of co-authors focused their experiments on the basic element by which literature is composed - namely, the language -, and conducted deep investigations on existing databases and unassisted corpus aiming at defining both a theoretical method and a precise technical procedure to be applied to literature. The essays presented in this book approach literature ranging from micro-linguistic dimensions to the larger scales of literary forms and genres through a series of quantitative measurements in order to increase, improve and develop a more precise understanding of ltheory and history of iterature.